A New Player in the “Synaptopathy” of Alzheimer’s Disease – Arc/Arg 3.1 - Kerrigan, Talitha L.; Randall, Andrew D. (Frontiers in Neurology, 2013)
Alzheimer’s disease (AD) is increasingly referred to as a “synaptopathy.” This moniker reflects the loss or damage of synapses that occurs as the disease progresses, which in turn produces functional degeneration of specific neuronal circuits and consequent aberrant activity in neural networks. Accumulating evidence supports the functional importance of the early-expression activity-regulated cytoskeletal (Arc) gene in regulating memory consolidation. Interestingly, AD patients express anomalously high levels of Arc protein. Arc physically associates with presenilin1, a pivotal protease for the generation of Amyloid β (Aβ) peptides. Arc expression itself is disrupted in the vicinity of Aβ oligomers and plaques. Such alterations result in the interruption of neuronal network integration in vivo. It is not clear what the impacts of these alterations are on the functional neurophysiology of transgenic mouse models of AD-associated amyloidopathy. Our group and others have described alterations to neuronal excitability and thus intrinsic firing within these transgenic mice models. This brief review will emphasize the rising role of Arc and its involvement in neurophysiological alterations of current AD models.